Light Pollution Intensity in the Aquatic Environment of the Oslo Area - FONTAINE, Romain; Gunnar Lindbo, Nils (Zenodo, 2024)
The rapid expansion of artificial lighting in urban areas has resulted in significant light pollution, with profound implications for both terrestrial and aquatic ecosystems. Artificial light interferes with the circadian rhythms of animals, impacting their behavior, reproduction, and migration patterns. For instance, birds and sea turtles that rely on moonlight for navigation can become disoriented by artificial lights, leading to fatal light attraction. Similarly, aquatic species may experience changes in their reproductive cycles and behavior due to altered light conditions. Previous studies observed that light pollution affects salmon migration and the reproductive timing of various fish species. While light pollution disrupts the natural light environment crucial for many aquatic species, the Oslo area includes two endangered species, the coastal cod and the wild Atlantic salmon which reproduce in coastal areas and rivers. This study thus focuses on invesitgating the extent of light pollution in the harbor and the Akerselva river in Oslo, Norway. Utilizing a quantum light pollution sensor, we measured light intensity at various depths in these water bodies during the winter of 2022. Our findings revealed measurable light pollution at all sampling points, including depths of up to 5 meters. Some locations exhibited light intensity levels nearly half as high as those measured under a streetlight, highlighting the severity of the issue. The study's findings highlights the pervasive nature of light pollution in urban aquatic environments and its potential to disrupt ecological processes. It underscores the need for wildlife-friendly lighting, urban planning guidelines, and increased awareness among the public and policymakers to mitigate the adverse effects of light pollution.